COUPLING SYSTEM OF CO2 CAPTURE IN FLUE GAS AND CO2 MINERALIZATION BASED ON INDUSTRIAL SOLID WASTE - Zhao, Huangjing; Zhou, Xiaozhou; Gao, Ming (2023)
A coupling system of CO2 capture in flue gas and CO2 mineralization based on industrial solid waste includes: 1) an adsorption reaction device configured to treat flue gas with the embedded adsorbents, 2) a thermal decomposition device designed to decompose the first carbonate products to oxides and carbon dioxide, wherein the produced oxides are circulated to the adsorption reaction device, and 3) an industrial solid waste mineralization system configured to treat the deactivated oxides and the as-produced carbon dioxide. The coupling system can not only realize carbon capture and utilization, but also can enable the reuse of waste and the production of high-quality carbonates. Meanwhile, the carbon capture line is also convenient to be organically integrated with the production line of carbon mineralization system based on industrial solid waste, reducing the cost of the whole process.